The Max-Planck-Institute global ocean/sea ice model with orthogonal curvilinear coordinates - Marsland, S.; Haak, H.; Jungclaus, J.; Latif, Mojib; Röske, F. (Ocean Modelling, 2003)
The Hamburg Ocean Primitive Equation model has undergone significant development in recent years. Most notable is the treatment of horizontal discretisation which has undergone transition from a staggered E-grid to an orthogonal curvilinear C-grid. The treatment of subgridscale mixing has been improved by the inclusion of a new formulation of bottom boundary layer (BBL) slope convection, an isopycnal diffusion scheme, and a Gent and McWilliams style eddy-induced mixing parameterisation. The model setup described here has a north pole over Greenland and a south pole on the coast of the Weddell Sea. This gives relatively high resolution in the sinking regions associated with the thermohaline circulation. Results are presented from a 450 year climatologically forced integration. The forcing is a product of the German Ocean Model Intercomparison Project and is derived from the European Centre for Medium Range Weather Forecasting reanalysis. The main emphasis is on the model's representation of key quantities that are easily associated with the ocean's role in the global climate system. The global and Atlantic northward poleward heat transports have peaks of 1.43 and 0.84 PW, at 18degrees and 21degrees N respectively. The Atlantic meridional overturning streamfunction has a peak of 15.7 Sv in the North Atlantic and an outflow of 11.9 Sv at 30degrees S. Comparison with a simulation excluding BBL shows that the scheme is responsible for up to a 25% increase in North Atlantic heat transport, with significant improvement of the depths of convection in the Greenland, Labrador and Irminger Seas. Despite the improvements, comparison with observations shows the heat transport still to be too weak. Other outstanding problems include an incorrect Gulf Stream pathway, a too strong Antarctic Circumpolar Current, and a too weak renewal of Antarctic Intermediate Water. Nevertheless, the model has been coupled to the atmospheric GCM ECHAM5 and run successfully for over 250 years without any surface flux corrections. (C) 2002 ...